A seven country comparison of nurses’ perceptions of their professional practice environment - Efstathiou, George; Agaroglou, Rengin; Papastavrou, Evridiki; Da Luz, Maria Deolinda Antunes; Berg, Agneta C.; Idvall, Ewa; Kalafati, Maria; Kanan, Nevin; Katajisto, Jouko K.; Leino-Kilpi, Helena T.; Lemonidou, Chryssoula; Şendir, Merdiye; et al. (My University, 2011)
Aims To describe and compare nurses perceptions of their professional practice environment in seven countries. Background There is evidence of variation in the nursing professional practice environments internationally. These different work environments affect nurses ability to perform and are linked to differing nurse and patient outcomes. Methods A descriptive, comparative survey was used to collect data from orthopaedic and trauma nurses (n = 1156) in Finland, Cyprus, Greece, Portugal, Sweden, Turkey and Kansas, USA using the 39-item Revised Professional Practice Environment instrument. Results Differences were found between participants from the northern countries of Europe, Kansas, USA, and the Mediterranean countries regarding perceptions about control over practice. No between-country differences were reported in the internal work motivation among the nurses from any of the participating countries. Conclusions Although between-country differences in nurses professional practice environment were found, difficulties related to demographic, cultural and health system differences and the way in which nursing is defined in each country need to be considered in the interpretation of the results.
Keywords: International; Nursing; Questionnaire; Cross-country comparison; Professional Practice Environment